Clinical Usefulness of Immunohistochemical Staining of p57kip2 for the Differential Diagnosis of Complete Mole. (16th June 2015) - Sasaki, Shigeru; Sasaki, Yasushi; Kunimura, Toshiaki; Sekizawa, Akihiko; Kojima, Yoshihiro; Iino, Koichi
Abstract : Objective . Can polymer-based immunohistochemical staining of p57 kip2 replace DNA analysis as an inexpensive means of differentiating complete mole from partial mole or hydropic abortion? Methods and Materials . Original paraffin-embedded tissue blocks from 14 equivocal cases were turned over to our laboratory and examined by immunohistochemical staining of p57 kip2 . Results . Four of the 14 cases showed clearly negative nuclear staining in cytotrophoblasts and villous stromal cells: these results were fully concordant with the control staining. The remaining 10 cases showed apparently positive staining in cytotrophoblasts and villous stromal cells. Without DNA analysis we are able to clearly differentiate the 4 cases of complete mole among the 14 equivocal cases. During follow-up, secondary low-risk gestational trophoblastic neoplasia (GTN) developed in 1 of the 4 cases of complete mole: the GTN was treated by single-agent chemotherapy. No subsequent changes were observed during follow-up in the other cases. Conclusion . Polymer-based immunohistochemical staining of p57 kip2 (paternally imprinted gene, expressed from maternal allele) is a very effective method that can be used to differentiate androgenetic complete mole from partial mole and hydropic abortion. We might be able to avoid the cost of DNA analysis.